MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI OPTIMALISASI LAYANAN BIMBINGAN BELAJAR SECARA KELOMPOK DAN INDIVIDU - Jamiatul Huda (FKIP ULM, 2013)
Research on Optimizing Service tutoring in students of the fourth class Layap Paringin MIN model is divided into two cycles. Each cycle consists of stages of planning, action, observation and reflection. Counseling services provided here are tutoring services as a group and individually. The action taken is to provide information to the students about the purpose of group learning, how to learn effectively,and overcoming problems in learning with group and individual counseling. ARCS questionaire was used to measure students’ motivation. The research concludes that the optimization of tutoring services for groups and individuals increased students’ motivation. It can be seen from the increased motivation of students in the first cycle reached 76.93% and 96.15% in the second cycle. Student motivation to attend the difficult lesson increased namely 78.85% after the first cycle I and 81.87% after the second cycle.